Il cibo come questione territoriale. Riflessioni alla luce della pianificazione alimentare - Cavallo, Aurora; Corchia, Ilaria; Di Donato, Benedetta; Marino, Davide (Scienze del Territorio, 2017)
In the recent years, agriculture has played a key role in reshaping rurality, in the view of a reconstruction of social and production structures accompanying the current re-territorialisation process, coming after a phase of de-territorialisation of the role of the agricultural sector as the focus of local balances. At the same time, the contemporary urban phenomenon is rewriting, even though not orderly, its relationship with agriculture and food, overcoming the traditional idea of city in which countryside is only extra muros. If the main experiences of the Italian food policies have concerned the great urban systems, the topic here discussed are food policies as an opportunity, offered to Italian small and medium-sized centres, to re-contextualise their own agro-food systems and their functions for the community. The ability of plans and policies to understand and orientate these processes shows, actually, growing difficulties. The breadth between civic or market practices and the regulatory, political and planning framework is territory, the place where we should build and experience new forms of governance, institutions and tools where citizenship, labour and market meet agriculture and territorial diversity. The paper focuses on the meaning and functions of food planning and discusses some possible implementation on the polycentric geography of the Italian territory.